pointblue/gdr_molt_sic: Schmidt et al. Sea ice concentration decline in an important Adélie penguin molt area - Annie Schmidt (Zenodo, 2023)
Code contained in this release was used in Schmidt et al. 2023. Sea ice concentration decline in an important Adélie penguin molt area. PNAS